Fisheries Adaptive Mechanism Analysis and Livelihood Vulnerability at Jakarta Bay - Robin, Robin (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
This study has two main objectives: 1) Analyzing the characteristic of fishermen in the Bay of Jakarta, 2) Building a conceptual model to see the relationship between the ecological footprint of fisheries and the vulnerability of livelihoods of fishermen. The data collection was done by triangulation method (observation, interview, and documentation). The sampling technique used snowball sampling with sample size were 15-30 samples. The method of analysis used in this research was descriptive qualitative for livelihood vulnerability based on Ellis’s (2000) equation and descriptive quantitative for fisheries ecological footprint (FEF). For FEF we used equation based on Pauly & Christensen (1995). The results showed that there was a quite different characteristic between fishermen in Kamal Muara, Muara Angke and Kalibaru related to tribes, fishing gear, income, adaptation model and education level. The livelihood vulnerability showed Fishermen at Muara angke much more vulnerable than fishermen at Kamal Muara and Kalibaru. For Fisheries ecological footprint showed that Jakarta bay ecosystem is overshot meant the biocapacity (BC) much lower than value of EF per capita for water system TS = 6,04 km2/fisherman, C & CS water system = 0,71 km2/fisherman and Non-TS = 0,42 km2/ fisherman while BC = 0,21 km2/fisherman..